2016
DOI: 10.1016/j.gdata.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Context based computational analysis and characterization of ARS consensus sequences (ACS) of Saccharomyces cerevisiae genome

Abstract: Genome-wide experimental studies in Saccharomyces cerevisiae reveal that autonomous replicating sequence (ARS) requires an essential consensus sequence (ACS) for replication activity. Computational studies identified thousands of ACS like patterns in the genome. However, only a few hundreds of these sites act as replicating sites and the rest are considered as dormant or evolving sites. In a bid to understand the sequence makeup of replication sites, a content and context-based analysis was performed on a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…The ACS is a loosely defined AT-rich 11–17 base pair sequence whose directionality is determined on the basis of the relative numbers of As versus Ts in the two strands ( Breier et al, 2004 ). This sequence is recognized by the Orc, a six-protein complex that loads MCM ( Bell and Stillman, 1992 ; Newlon and Theis, 1993 ; Berbenetz et al, 2010 ; Eaton et al, 2010 ; Singh and Krishnamachari, 2016 ). Although the characteristics that allow a sequence to serve as an Orc binding site remain poorly understood, with, for example, only approximately half of the origins listed in SGD reporting associated ACS signals, researchers have calculated a probability weight matrix to evaluate the fidelity of the correspondence of any 17 base pair sequence with a hypothetically ‘perfect’ ACS ( Coster and Diffley, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ACS is a loosely defined AT-rich 11–17 base pair sequence whose directionality is determined on the basis of the relative numbers of As versus Ts in the two strands ( Breier et al, 2004 ). This sequence is recognized by the Orc, a six-protein complex that loads MCM ( Bell and Stillman, 1992 ; Newlon and Theis, 1993 ; Berbenetz et al, 2010 ; Eaton et al, 2010 ; Singh and Krishnamachari, 2016 ). Although the characteristics that allow a sequence to serve as an Orc binding site remain poorly understood, with, for example, only approximately half of the origins listed in SGD reporting associated ACS signals, researchers have calculated a probability weight matrix to evaluate the fidelity of the correspondence of any 17 base pair sequence with a hypothetically ‘perfect’ ACS ( Coster and Diffley, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ACS is a loosely defined AT-rich 11-17 base pair sequence whose directionality is determined on the basis of the relative numbers of As versus Ts in the two strands (Breier et al 2004 ). This sequence is recognized by the Origin Recognition Complex (Orc), a 6-protein complex that loads MCM (Bell and Stillman 1992 ;Newlon and Theis 1993 ;Eaton et al 2010 ;Singh and Krishnamachari 2016 ). Although the characteristics that allow a sequence to serve as an Orc binding site remain poorly understood, with, for example, only approximately half of the origins listed in SGD reporting associated ACS signals, researchers have calculated a probability weight matrix to evaluate the fidelity of the correspondence of any 17 base pair sequence with a hypothetically "perfect" ACS (Coster and Diffley 2017 ).…”
Section: Binding Sites Are Flanked By Acs Sequences and MCM Is Loaded...mentioning
confidence: 99%
“…1. "This sequence is recognized by the Origin Recognition Complex (Orc), a 6-protein complex that loads MCM (Broach et al, 1983;Deshpande and Newlon, 1992;Eaton et al, 2010;Kearsey, 1984;Newlon and Theis, 1993;Singh and Krishnamachari, 2016;Srienc et al, 1985)." This list should include a reference to Bell and Stillman, 1992 (PMID: 1579162), which first described ORC and showed that it recognized the ACS.…”
Section: Data Availabilitymentioning
confidence: 99%
“…The ACS is a loosely defined AT-rich 11-17 base pair sequence whose directionality is determined on the basis of the relative numbers of As versus Ts in the two strands (Breier et al, 2004). This sequence is recognized by the Origin Recognition Complex (Orc), a 6-protein complex that loads MCM (Broach et al, 1983;Deshpande and Newlon, 1992;Eaton et al, 2010;Kearsey, 1984;Newlon and Theis, 1993;Singh and Krishnamachari, 2016;Srienc et al, 1985). Although the characteristics that allow a sequence to serve as an Orc binding site remain poorly understood, with, for example, only approximately half of the origins listed in SGD reporting associated ACS signals, researchers have calculated a probability weight matrix to evaluate the fidelity of the correspondence of any 17 base pair sequence with a hypothetically "perfect" ACS (Coster and Diffley, 2017).…”
Section: Acssmentioning
confidence: 99%
“…The ACS is a loosely defined AT-rich 11-17 base pair sequence whose directionality is determined on the basis of the relative numbers of As versus Ts in the two strands (Breier et al 2004). This sequence is recognized by the Origin Recognition Complex (Orc), a 6-protein complex that loads MCM (Bell and Stillman 1992;Newlon and Theis 1993;Eaton et al 2010;Singh and Krishnamachari 2016).…”
Section: Acssmentioning
confidence: 99%